Study of knowledge and perception of hand hygiene among nursing staff in a tertiary care hospital - Nikam, Archana P.; Bhise, Pramod R.; Deshmukh, Mukta M. (International Journal of Research in Medical Sciences, 2025)
Background: Health care-associated infections (HAIs) are a major cause of morbidity and mortality, significantly impacting hospitalized patients. Poor hand hygiene among healthcare workers is a primary contributor to these infections, leading to longer hospital stays, increased antibiotic resistance, and substantial financial burdens. Nurses, being the largest group of healthcare workers with extensive patient contact, play a crucial role in preventing HAIs through proper hand hygiene. This study aimed to assess nurses’ knowledge and perceptions of hand hygiene to inform strategies for promoting effective practices. Methods: This cross-sectional, questionnaire-based study was conducted at a tertiary care hospital, involving 234 nursing staff. Participants provided verbal consent. The study utilized the WHO hand hygiene knowledge questionnaires. Scores were converted to percentages and categorized as good (>75%), moderate (50-75%), or poor (<50%). Incomplete questionnaires were excluded. Data was kept confidential, validated by a pilot test, and analysed using SPSS version 23. Results: The study included 234 predominantly female (92.73%) and young (62.39% aged 20-30) nursing staff; 96% had received formal hand hygiene training. Regarding knowledge, 62.82% had moderate knowledge, 32.90% had poor knowledge, and only 4.27% demonstrated good knowledge. For perception, a significant majority (80.34%) showed good perception, with 12.39% moderate and 7.26% poor. Gaps were identified in understanding germ sources and the effective use of hand rubs/washes. Conclusions: The study findings highlight the critical need for tailored, ongoing training programs focusing on practical demonstrations, clarification of germ sources, and effective application methods.